Gestational diabetes awareness in women of childbearing age in Sharjah - Amr Elmekresh; Batool AbuHalimeh; Rawan Abukhater; Amina Bakro; Samher Nahab (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2017)
Objectives: Gestational diabetes mellitus (GDM) is a current health problem that affects a large number of female population and has deleterious impact on both the mother and the child. The aim of this study is to assess the awareness of GDM among females in the childbearing age in Sharjah community. Study Design: study is a quantitative "cross-sectional" descriptive. The study subjects have been chosen to represent the population, and all the data will be collected over a specific period of time (3 weeks). Methods: In this cross-sectional study awareness about GDM in females of general population aged between 18-45 years was assessed. A validated questionnaire was used. Responses were scored from 0-39, a score of 19 indicated awareness. Data was analyzed using Chi-square independent T-test for bivariate analysis, via SPSS21 software.  Results: Four hundred and fifty women participated in the study, of whom 73.5% were aware of the disease. Married women had a higher level of awareness compared to non-married women (M=14.8, 12.44 respectively,); t (390)=2.46, p = 0.01. Awareness between Emirati and non-Emirati wasn't significant, (M=13.80M=13.01, respectively) ; t (402)=1.00, p = 0.32 , Also a Chi-square test revealed no relationship was found between Age and the level of awareness of GDM , X2 (24, N = 450) = 21.42, p =0.61, as well as no relationship between level of Education obtained and the level of awareness of GDM , X2 (24, N = 450) = 19.92, p =0.70. Although the physicians and healthcare providers were the source of information about GDM in only 19.4% of the sample, they are still the most preferable method to get knowledge about the disease. Conclusion: Although the awareness of GDM as a disease in Sharjah community is high, the depth of knowledge was poor.